Antioxidant Activity of Medicinal Herbs and Spices from Plants of the Lamiaceae, Apiaceae and Asteraceae Families: Chemometric Interpretation of the Data - Beata Ulewicz-Magulska; Marek Wesolowski (MDPI AG, 2023)
Plant products, especially medicinal herbs and spices, have been used for centuries as a remedy to support human health and improve the flavor of food. Therefore, the purpose of this study was to identify plant species distinguished by their high content of phenolic compounds and high antioxidant activity using advanced multivariate statistical techniques such as Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA). To realize the purpose of the study, the total phenolic (TPC) and flavonoids (FC) content, antioxidant activity (TAC) and Fe(II) ion chelating capacity (FIC) of medicinal herbs and spices from plants belonging to three botanical families, Lamiaceae, Apiaceae and Asteraceae were determined. The interpretation of the obtained data revealed that the studied samples are localized in the PCA and HCA plots according to their TPC, FC, TAC and FIC values. Chemometric analysis confirmed that medicinal herbs and spices from plants belonging to the Lamiaceae family are richer sources of phenolic compounds and exhibit stronger antioxidant activity than those raw materials from plants in the Apiaceae family. In addition, no significant differences were found in terms of TPC, FC, TAC and FIC values between medicinal herbs and spices from the same plant species, i.e., oregano (Origanum vulgare), common thyme (Thymus vulgaris), rosemary (Rosmarinus officinalis), caraway (Carum carvi) and lovage (Levisticum officinale). A close relationship between antioxidant properties and contents of phenolic compounds was also confirmed.